The Influence of Innovation Leadership on Employee Performance - Nana Supriatna; Zulganef Zulganef (Research Collaboration Community (RCC), 2023)
The last few decades have seen significant research in the fields of innovation and leadership. The act of motivating, influencing, and directing team members toward the intended objectives is referred to as leadership. However, the term of leadership is broad and has various definitions. It encompasses and influences a range of methods, circumstances, aptitudes, and attributes. On the other side, innovative leaders are creative thinkers who may produce concepts that serve as the foundation for innovation. Understanding the principles of leadership and innovation is essential before one can fully comprehend the true meaning of innovative leadership. This study combines the two terms, reviews the innovative leadership style that will be discussed in the literature, and gives a general summary of how the two terms affect employees' performance.